Design of SPDT Switch with CMOS for application at 2.4GHz - See, Xue Kang (Nanyang Technological University, 2020)
The use of mobile devices has become important part of our life. Being able to source for important information and contact one another from any location and time is greatly contributed by wireless communication technologies. One major component in wireless technology is the Transmit/ Receive (T/R) Switch, a simple T/R switch allows transmitting and receiving to be shared by one antenna removing the need for having 2 antennas. In this project, the design process of a simple Single Pole Double Throw (SPDT) T/R Switch using STM 65nm CMOS Technology will be explored. From the study of SPDT Switch topology to designing the schematic drawing and finally Layout design.